2016
DOI: 10.1007/s11427-016-5060-3
|View full text |Cite
|
Sign up to set email alerts
|

Etiological characteristics of chlamydia trachoma conjunctivitis of Primary Boarding School students in the Qinghai Tibetan area

Abstract: The aim of this study was to investigate the etiological characteristics of Chlamydia trachomatis conjunctivitis among resident students at primary schools in the Qinghai Tibetan area in order to understand the distribution of C. trachomatis and other pathogenic microorganisms, to detect the isolation rate of infectious pathogens, and to provide an evidence for further targeted efforts in the prevent of sporadic trachoma efforts. From two primary schools in Qinghai Province, ocular samples from 35 students who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Children resident in boarding schools investigated in this study were found to have clinical evidence of active trachoma (conjunctival lymphoid follicles) during this survey. Thus, a complete trachoma screening and sampling was performed in order to understand the prevalence and etiology of trachoma in these schools (Li et al, 2016; Wang M. et al, 2016). The Wang group identified 45 cases of follicular conjunctivitis, 26 of them were infected with ompA genovar B C. trachomatis , and identified other potential follicle-causing bacteria in both C. trachomatis -positive and—negative cases (Li et al, 2016; Wang, 2016; Wang M. et al, 2016; Wang N. et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children resident in boarding schools investigated in this study were found to have clinical evidence of active trachoma (conjunctival lymphoid follicles) during this survey. Thus, a complete trachoma screening and sampling was performed in order to understand the prevalence and etiology of trachoma in these schools (Li et al, 2016; Wang M. et al, 2016). The Wang group identified 45 cases of follicular conjunctivitis, 26 of them were infected with ompA genovar B C. trachomatis , and identified other potential follicle-causing bacteria in both C. trachomatis -positive and—negative cases (Li et al, 2016; Wang, 2016; Wang M. et al, 2016; Wang N. et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a complete trachoma screening and sampling was performed in order to understand the prevalence and etiology of trachoma in these schools (Li et al, 2016; Wang M. et al, 2016). The Wang group identified 45 cases of follicular conjunctivitis, 26 of them were infected with ompA genovar B C. trachomatis , and identified other potential follicle-causing bacteria in both C. trachomatis -positive and—negative cases (Li et al, 2016; Wang, 2016; Wang M. et al, 2016; Wang N. et al, 2016). Their identification of non-chlamydial bacteria in clinically identified cases of follicular trachoma is congruent with other studies (Burton et al, 2011; Burr et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 43 ] Copan swabs were recommended for sample collection. [ 44 ] Several testing methods, such as culture, serology, immunofluorescence test, complement fixation test and PCR were applied in detection. The strain can only be acquired through cell culture.…”
mentioning
confidence: 99%
“…Meanwhile, Mei Wang et al observed that Chlamydia trachomatis infections were present with multiple bacteria, particularly Haemophilus influenzae, Staphylococcus aureus, Moraxella catarrhalis, and Streptococcus pneumoniae in 57.14% of cases, while single Chlamydia trachomatis infections accounted for 42.86% of cases (Wang et al, 2016). Qingfeng Liang et al reported a high prevalence (34.29%) of infectious conjunctivitis among rural primary school students in the Qinghai province.…”
mentioning
confidence: 99%